The Antibiotic Puzzle: Guidelines for the Family Physician - G Harding; S Field; R MacMahon; T Louie; Prairie Consensus Conference Group (Canadian Journal of Infectious Diseases)
Choosing the most appropriate antibiotic for the treatment of common infections is becoming increasingly complex. New drugs and new classes of antibiotics are being developed and made available, and emerging resistance and pharmacoeconomics play important roles. The Canadian healthcare system presents a unique challenge for prescribing physicians because pharmacoeconomic considerations are becoming increasingly important. It is important that Canadian guidelines be developed to address the needs of Canadian physicians. A consensus conference was held in October 1996 to discuss appropriate guidelines for antibiotic recommendations for common adult respiratory, urinary tract and diabetic foot infections. In August 1997, the guidelines were reviewed and updated as part of a second meeting of the group on antimicrobial resistance. The final recommendations constitute the information in this document. The panel of physicians and pharmaceutical doctors from the Prairie provinces of Alberta, Saskatchewan and Manitoba included family physicians and specialists in internal medicine, respirology, urology, infectious diseases, medical microbiology and pharmacoeconomics.